Process as Rheme Proper in Lithuanian and English Sentences - Petronienė, Eglė (Kalbotyra, 2003)
The article presents an analysis of Lithuanian and English sentences perspectived towards a process. The communicative function of the process depends on whether the sentence is contextualized or not: the communicative structure of context-independent and contextualized sentences may differ considerably.In context-independent intransitive sentences expressing processes which are not accompanied by circumstantials, the process is communicatively neutral: it may function as the theme or the rheme. When accompanied by a circumstantial, the process is less informative than the circumstantial which is the rheme proper. In context-independent transitive sentences, the process is extended to participants which take the communication further and thus function as the rheme proper.In contextualized sentences, processes function either as the theme or as the rheme. In Lithuanian, there is a strong tendency to arrange sentence elements in accordance with a gradual rise of CD. Thus, the process takes a position in the sentence depending on its informativity. When it is most communicatively important the process is expressed by the verb in sentence-final position. When it is not the verb is followed by more informative sentence elements.English does not differ from Lithuanian as regards intransitive sentences with a thematic subject. In transitive sentences, the verb whether thematic or rhematic takes non-final position in the sentence. Its actual function is determined by the context.